Factors influencing the development of transplantation in Africa - Gool, Ferhana (Department of Surgery, 2020)
Background Access to dialysis and transplantation in Africa is very limited. The challenges vary in different countries across the continent from legislative, to political, to financial. Aim To assess factors influencing the development of organ donation and transplantation in the African context. Methods A structured interview was held with African delegates attending the 25th Southern African Transplantation Society Congress and Global Alliance for Transplantation Workshop in Durban from the 28th July to 2nd of August 2013. Data from workshop working group presentations for each African country were additionally analysed. Results 30 delegates from 10 African countries (Cameroon, Ethiopia, Ghana, Kenya, Malawi, Nigeria, Rwanda, Tunisia, Sudan and Zambia) participated in the working groups. Twenty-eight questionnaires were completed. The burden of disease and challenges were large and varied. With marked disparity between countries where kidney transplantation is paid for entirely out-of-pocket—such as Ghana, Kenya, and Nigeria (kidney transplant rates in 2012 of 0.1, 1.4 and 0.1 per million population respectively)—and countries where costs are covered by the government or by insurance schemes—such as Sudan and Tunisia (kidney transplant rates of 5.3, and11.5 per million population, respectively). For most countries, the cost of immunosuppressive drugs and the ability to perform adequate matching of donors and recipients were the main infrastructure concerns. Five countries (Cameroon, Nigeria, Ghana, Ethiopia, Zambia) did not have legislation governing organ transplantation. Conclusion There is need for major political transform which will to ensure that African populations achieve access to transplantation. This would allow international collaboration and willing local clinicians a framework within which to develop sustainable transplant systems.